Capital accumulation, the choice of techniques, and agricultural output - Mundlak, Yair (International Food Policy Research Institute, 1988)
Economic growth is achieved largely through capital accumulation and technical change. However, these two processes are not independent. Generation of technical change requires resources and in this sense can be considered to be an investment activity, as is recognized by calling cumulative investment in nonphysical capital "human capital." The implication is that the rate of growth of the economy depends, to a large degree, on the rate of capital accumulation. This chapter will discuss some aspects of the structure of this interdependence between capital accumulation and technical change. The emphasis will be on agriculture, but many of the propositions are of a general nature.